Suppression of OsMDHAR4 enhances heat tolerance by mediating H2O2-induced stomatal closure in rice plants - Jianping Liu; Xinjiao Sun; Feiyun Xu; Yingjiao Zhang; Qian Zhang; Rui Miao; Jianhua Zhang; Jiansheng Liang; Weifeng Xu (Rice, 2018)
Abstract Background Monodehydroascorbate reductase (MDAR or MDHAR), which is responsible for growth, development and stress response in plants, is a key enzyme in the maintenance of the ascorbate acid (AsA) pool through the AsA–glutathione (AsA–GSH) cycle. High temperature affects a broad spectrum of cellular components and metabolism including AsA–GSH cycle in plants. In rice, however, the detailed roles of OsMDHAR4 in resistance against heat stress remains unclear. Results Here, we report that OsMDHAR4 protein was localized to the chloroplasts. OsMDHAR4 expression was detected in all tissues surveyed and peaked in leaf blade. OsMDHAR4 was responsive to multiple stresses and was relatively strongly induced by heat treatment. In comparison with wild type, the osmdhar4 mutant exhibited improved tolerance to heat stress, whereas OsMDHAR4 overexpression lines exhibited enhanced sensitivity to heat stress. Moreover, we found that suppression of OsMDHAR4 promoted stomatal closure and hydrogen peroxide accumulation, and overexpression of OsMDHAR4 increased stomatal opening and decreased hydrogen peroxide content in rice leaves. Conclusions Taken together, these results indicated that OsMDHAR4 negatively regulates tolerance to heat stress by mediating H2O2-induced stomatal closure in rice.